Indefeasibility and equitable intervention in the Malaysian torrens system / Ahmad Nazri Ibrahim - Ibrahim, Ahmad Nazri (Faculty of Law, 1986)
In relation to its concept. effect of and exceptions to Indefeasibility of title in the Torrens system represents a very interesting area of study in Land Law. The very Central concept of Torrens system of registration is the Indefeasibility of title, the registered proprietor being given a sheild of protection against any adverse claim as against the title of the landed Property. Section 340 of the National Land code confers upon registration to a registered proprietor of land an Indefeasible title. However the fact remains that notwithstanding the concept of Indefeasibility as pointed out by Lord Wilberforce in FRAZER V NALKER (1967) 1 ALL.E.R. 649. Indefeasibility itself is never absolute. Not only does Section 340(2) of the Code provides for specific statutory exceptions to Indefeasibility of title but the court have also in nature of exceptions made equitable Incursions attacking the very basis of the Concept of Indefeasibility. The courts have stated that equity will step in to prevent the Machinery of the Act of Parliament being used to defeat equities. The Torrens System has not abrogated the principles of équity and its application but only so far as it is necessary to attain its own special objects it has altered the application of equity